Project learning in construction - Hamzah Abdul Rahman; Wang, Chen; Faizul Azli Mohd Rahim; Nurshuhada Zainon; Ali Mohammed Alshwal (University of Malaya Press, 2013)
This book focus on project learning un construction rather than entire organizational learning which is applied through the concepts of knowledge management